Research on optimal heat input parameter for TIG welding of thin plate 5083 aluminum alloy - Wei Guo; Xincheng Zhao; Yonglin Zhao; Yuxiang Liu; Han Li; Bingyuan Han (Scientific Reports)
Abstract Heat input represents a critical process parameter that significantly influences the quality of tungsten inert gas (TIG) welding. In this study, a comprehensive investigation of heat input effects on the welding quality of thin-gauge aluminum alloy was conducted through integrated theoretical analysis and experimental validation. The research established an optimal heat input range of 296–321 J/mm for 3 mm thick 5083 aluminum alloy plates in TIG welding applications, within which welded joints demonstrated minimal defect formation and superior mechanical performance. Both numerical simulations and experimental results revealed a distinct non-monotonic relationship between heat input and joint properties: when operating below the optimal range, progressive increases in heat input resulted in corresponding improvements in fusion characteristics and mechanical properties. Conversely, exceeding the optimal range led to progressive grain coarsening within the weld microstructure, accompanied by measurable degradation in key mechanical properties including tensile strength and hardness.